IDENTIFIKASI IRIS MATA MENGGUNAKAN TAPIS GABOR WAVELET DAN JARINGAN SYARAF TIRUAN LEARNING VECTOR QUANTIZATION (LVQ) - Budi Setiyono; R. Rizal Isnanto (Diponegoro University, 2009)
Biometric represents the human identification method development using natural characteristic of humanbeing as its bases. Every iris has the detail and unique texture, even differ between right and left eye.Theeye iris identification process in this research are data acquisition, early processing, feature exctractionand classification. Algorithm used for classification of texture slice the eye is Gabor wavelet filtering, andclassification process of slice the eye texture will be used by a Artificial Neural Network LVQ. Recognitionthe value of feature vektor in each iris obtained from to the number of right recognition value or thepercentage of right one. The best recognition percentage is 87,5 %.